The adaptive role of emotional self-regulation in adolescents’ well-being: evidence from Chilean public schools - Fuentealba-Urra, Sergio; Céspedes-Carreno, Cristian; Rubio, Andrés; Roy-Sadradín, Damarys; Oyanedel, Juan Carlos; Martínez-Líbano, Jonathan; Leigh-González, Camila; González-Carrasco, Mònica; Zapata, Silvina Maria; Arellano-Correa, Sandra; Urrutia-Díaz, Víctor; Fuentealba-Martín, Cristian (Frontiers in Education, 2026)
IntroductionSubjective well-being (SWB) serves as a key indicator for assessing psychosocial adjustment and quality of life in adolescence. The established connection between emotional self-regulation (ESR) and well-being is well documented, yet the specific role of short-term ESR strategies and sociodemographic factors remains underexplored. This study examines how short-term ESR and these sociodemographic variables jointly influence the subjective well-being (SWB) of Chilean adolescents.MethodsA cross-sectional design utilized a stratified probabilistic sample of 917 students (49.2% girls, 50.8% boys), aged 10–19. Participants came from public schools in the Biobío region. All institutions were classified with high or very high vulnerability based on the School Vulnerability Index.ResultsMultiple regression analysis revealed that higher ESR and male gender predicted greater well-being scores. Conversely, lower results emerged for female participants, older age, and high vulnerability. After controlling age, gender, and migration status, very high vulnerability was associated with slightly higher well-being, suggesting a compensatory effect when other conditions were equalized. ESR acts as a protective factor for adolescent well-being amid educational inequality.DiscussionIntegrating socioemotional competencies into school-based psychological services is therefore imperative. Intervention and public policies promoting adolescent well-being must account for gender, age, and vulnerability status in their design.